Extraction of Lutein from Banana Peel via Ultrasound-Assisted Extraction Method for the Formulation of Antioxidant Soap - Kokilam K.Renggasamy; Elizah Mohamed (Progress in Engineering Application and Technology, 2026)
Banana peels are normally discarded, although they possess precious bioactive compounds like lutein, which is a xanthophyll-carotenoid pigment that has been found to possess a high antioxidant capacity. The goal of this work is to extract lutein from yellow and green banana peels using the Ultrasound-Assisted Extraction (UAE) technique and to determine the effect of ethanol concentrations (50% and 96%) on lutein extraction using UV-Visible spectroscopy at 450nm. Additionally, the lutein extracts from the UAE process will be analyzed with the use of Fourier Transform Infrared Spectroscopy (FTIR) to identify functional groups that are characteristic of carotenoids. The antioxidant capacity was determined using the DPPH assay at a wavelength of 517nm for all four lutein extracts (Y96, G96, Y50, and G50). The concentrated lutein extract was used to prepare an antioxidant soap using the cold saponification process, and the product was analyzed for its physical and chemical properties, which include pH (8-9), foamability (80%), foam stability (77.95%), moisture content (8.31%), and organoleptic tests, in addition to analyzing its DPPH radical scavenging activity (7.31%). The results of the work show that banana peels are a good source of lutein, and the UAE process is effective in the extraction of heat-sensitive compounds, in addition to contributing to the design of an environmentally friendly cosmetic material from agro-industrial waste.